DEVELOPMENT OF A CLASSIFICATION SYSTEM BASED ON KINEMATIC AND PSYCHO-PHYSIOLOGICAL CHARACTERISTICS FOR TRAINING RESERVE ATHLETES FOR PARALYMPIC SPORTS COMPETITIONS (Scientific journal of the Fergana State University, 2024)
This article discusses the kinematic and psychophysiological features of the preparation of athletes-reservists for Paralympic sports competitions, reveals the possibility of movement of an athlete for a transitional period after the competition and the essence of this period for the next stages of preparation. One of the main goals of field scientists is to introduce tools and methods into the educational process that will give excellent results in a short period of time. The results of this study reveal the results of the kinematic analysis of the chosen method of performing these loads, which are selected for each stage of the preparation of para-athletes.